Does the Level of Confidence Exhibited by Dental Students Predict the Outcome of Complete Denture Therapy? - Indika P. Thilakumara; Kaumudi U. Prathibhani; Sumudu G. K. Rasnayaka; Sachith P. Abeysundara; Rasika M. Jayasinghe (Hindawi Limited, 2020)
Purpose/Objectives. Development of self-confidence is as important as competency in technical and clinical skills of a dental student. This study assessed the association of the level of confidence in dental students with the level of satisfaction of patients and the clinical outcome in the management of complete denture patients. Materials and Methods. Fifty-seven final-year dental students in the year 2019 and the first edentulous patient managed by them were recruited for the study. A fourteen-item questionnaire was given to the students to assess their level of confidence just before commencement of the treatment. Questionnaire for the patients was used to assess their satisfaction both with the operator and the dentures. Clinical outcome of dentures was assessed using ten criteria. Results. The average confidence level of the students was found to be 2.17 in a 4-point scale. A two-sample test indicated that there is a significant difference in the overall level of confidence between female and male students (p value = 0.004). Moreover, a nonparametric correlation analysis revealed that there is no significant correlation between the overall level of confidence of each student and patient satisfaction regarding student performance, level of satisfaction of patients regarding dentures, and the quality of dentures as assessed by the clinicians (p value = 0.545, 0.877, and 0.801, respectively). Conclusions. Students' level of confidence in carrying out complete denture procedures is satisfactory. Male students exhibited a better overall level of confidence than female students. However, the level of confidence exhibited by the dental students does not predict patient satisfaction or clinical outcome.